A solid-solution approach for controllable photomechanical crystalline materials - Yang Ye; Di Wu; Ying Sun; Dechen Wang; Yuanhang Wang; Na Wang; Hongxun Hao; Liang Li; Panče Naumov; Chuang Xie (Nature Communications)
Abstract Solid solutions are a unique and elegant crystal engineering strategy to control the properties of crystalline materials, and the tunability of physicochemical properties it provides has a wide scope of applications. In this research, we bring this strategy to the realm of smart molecular crystals and explore solid solutions of organic photomechanical crystals to create flexible structures that exhibit a gradient of predetermined emissive, mechanical, and reactive properties. Specifically, we demonstrate that fluorescence, mechanical properties, and solid-state photoreactivity in a binary mixed crystal system of 9-anthraldehyde (9AA) and 9-methylanthracene (9MA) can be simultaneously and precisely tuned simply by changing the composition. The statistical distribution of the two components in the solid solution was utilized to prepare a heterodimer by a cross-reaction between the molecules of the two components. The effect of doping on the rate and the extent of the solid-state photoreaction further enables modulation of the photomechanical bending of the crystals. This study shows that the solid solution method enables access to smart adaptive crystals that can perform specific solid-state photoreactions, exhibit a photomechanical response, and support flexible organic devices that cannot be achieved through conventional chemical modification strategies.